2011
DOI: 10.1177/0961203311398264
|View full text |Cite
|
Sign up to set email alerts
|

Coping with health-stressors and defence styles associated with health-related quality of life in patients with systemic lupus erythematosus

Abstract: This study aimed to assess the association of coping with health-stressors and defence styles with health-related quality of life (HRQOL) in systemic lupus erythematosus (SLE). In 56 SLE patients we assessed disease activity (SLEDAI), functional limitations (HAQ), psychological distress (SCL-90-R), defence styles (Defence Style Questionnaire), hostility (HDHQ), coping with health-stressors (Sense of Coherence scale) and HRQOL (WHOQOL-BREF). Two hundred and eight rheumatologic patients (168 with rheumatoid arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…Two studies found that the sense of coherence (soc) is a strong correlate of hrqol in patients with sle (Abu-Shakra et al, 2006;Hyphantis, Palieraki, Voulgari, Tsifetaki & Drosos, 2011). This construct theory hypothesizes that an individual with a strong soc maintains and improves health through effective coping with stressors and flexibility, for the purpose of facilitating the adoption of preventive behaviors related to health and eliminating unhealthy ones, while low levels of soc correspond to individuals with low perceived competence to overcome the health stressors (Hyphantis, et al, 2011). Thus, a person with a strong soc would be able to cope with stressors related to illness, and therefore enjoy a better qol (AbuShakra et al, 2006).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found that the sense of coherence (soc) is a strong correlate of hrqol in patients with sle (Abu-Shakra et al, 2006;Hyphantis, Palieraki, Voulgari, Tsifetaki & Drosos, 2011). This construct theory hypothesizes that an individual with a strong soc maintains and improves health through effective coping with stressors and flexibility, for the purpose of facilitating the adoption of preventive behaviors related to health and eliminating unhealthy ones, while low levels of soc correspond to individuals with low perceived competence to overcome the health stressors (Hyphantis, et al, 2011). Thus, a person with a strong soc would be able to cope with stressors related to illness, and therefore enjoy a better qol (AbuShakra et al, 2006).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Dobkin et al, 1999;Rinaldi et al, 2006;Da Costa et al, 2000;Friedman et al, 1999;Abu-Shakra et al, 2006;Bennett, Fuertes, Keitel & Phillips, 2011;Dobkin et al, 2002;Haupt et al, 2005;Dobkin et al, 2001) who qol-Brief scales 2 (Hyphantis et al, 2011;Abu-Shakra et al, 2006) Focus groups 1 (Robbins, Allegrante, & Paget, 1993;Beckerman, 2011) Coping: The Coping Style Inventory (csi) 1 (Kozora, et al, 2005) Freiburg questionnaire on coping with illness (fkv) 1 (Haupt et al, 2005) The Coping Orientation to Problems Experienced (cope) 1 (Rinaldi et al, 2006) Lupus erythematosus needs questionnaire (slenq) 1 (Auerbach, Beckerman & Blanco, 2013) Lupuspro 1 (Jolly et al, 2014) General Health Questionnaire-30 (ghq-30) 1 (Ng & Chan, 2007) Coping skills 10 items questionnaire designed by Arthritis Foundation. 1 (Sohng, 2003) Focus groups 3 (Beckerman, 2011;Beckerman & Sarracco, 2012;Robbins, Allegrante & Paget, 1993) in different significant domains of life experience, such as social relationships, personal development and intimacy.…”
Section: Copingmentioning
confidence: 99%
“…No study to date has examined how coping cognitions specific to pain may influence important outcomes, such as pain, stiffness, fatigue, and mood, in SLE patients. Past studies in patients with SLE have demonstrated that patients' general coping strategies and perceptions of control (i.e., not specifically related to SLE pain) are related to SLE disease activity (2,6 -8), physical functioning (9), psychological functioning (2,10), and other measures of quality of life (11). Two pain coping cognitions that may be particularly important to consider in patients with SLE are self-efficacy for pain control and pain catastrophizing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of SOC scale detect those patients who are coping poorly with the illness because they have poor psychological resources, in order to promote psychotherapeutic interventions that improve patients' QOL. (Abu-Shakra et al, 2006;Hyphantis et al, 2011) …”
Section: Sense Of Coherencementioning
confidence: 99%